Evaluation of Changes in the Branch and Educational Structure of the Labour Force in the Czech Republic with an Emphasis on Manufacturing and Services - Šerý, Ondřej; Toušek, Václav (Studies of the Industrial Geography Commission of the Polish Geographical Society, 2013)
This paper deals with the evaluation of changes in the labour force in the Czech Republic after 1989 and focuses on the branch and educational structure. The changes are also compared with processes in other countries of Central Europe. In the late 1980s the employment rate by sectors of the economy was different in Central European countries when compared with the situation in Western countries. Even subsequent transformation did not change the high share of industry and construction in total employment in the Czech Republic and Slovakia or a lower share of services. Within the manufacturing industry two stages can be distinguished. In the nineties, the majority of branches experienced a decrease in employment, whereas in the first decade of the 21st century stagnation or even reindustrialization occurred, especially when the branches associated with the automotive industry grew (other branches continued to decline). At the regional level, a diversification process was taking place all the time, if you like the transition from the specialization to the diversification. The importance of education is constantly increasing and the number of people with secondary education with GCE and tertiary education is growing. The relationship between the unemployment rate in districts of the Czech Republic and the share of employed people with tertiary education intensifies. The tertiary sector shows the highest level of education (in some branches of services more than onethird of employed has a tertiary education).